KONTRIBUSI PRESTASI PRAKTIK KERJA INDUSTRI DAN PENGETAHUAN TENTANG DUNIA INDUSTRI DENGAN MINAT KERJA DI BIDANG OTOMOTIF - frengki bahtiar; slamet priyanto; nurcholish arifin handoyono (Program Studi Pendidikan Vokasional Teknik Mesin, Universitas Sarjanawiyata Tamansiswa, 2020)
The purpose of this study was to determine how much (1) the contribution of industrialwork practice achievement and knowledge of the industrial world together with student workinterest in the automotive sector, (2) the contribution of industrial work practice achievement to student work interest in the automotive sector, (3) knowledge of the industrialworld with the student's work interest in the automotive field. This type of research is ex- post facto research with a population of 77 students of class XII of the Light Vehicle Engineering Expertise Program. Because the population is less than 100, the whole sampleis 77 students and this research is called a populative research. The data collection instrument used a questionnaire and documentation. The data analysis technique used descriptive statistics; the analysis prerequisite test used the normality, linearity, and multicollinearity test; and hypothesis testing using partial correlation. multiple correlation,and F test with multiple regression analysis. The results showed that: (1) the achievement ofindustrial work practices and knowledge of the industrial world together gave a positive andsignificant contribution of 54% towards students' work interest in the automotive sector; (2)the achievement of industrial work practice gave a positive but insignificant contribution of0.6% to students' work interest in the automotive sector; (3) knowledge of the industrial world gave a positive and significant contribution of 53.2% to students' work interest in theautomotive sector.